2009
DOI: 10.1111/j.1399-6576.2009.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of intra‐operative hypotension varies between hospitals: observational analysis of more than 147,000 anaesthesia

Abstract: Wide variations remain in the occurrence of hypotension among hospitals after adjustment for risk factors. Although differential reporting from hospitals may exist, variations in anaesthesia techniques and blood pressure maintenance may also have contributed. Intra-operative hypotension is associated with morbidities and sometimes death, and constant vigilance must thus be advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
(63 reference statements)
0
24
1
3
Order By: Relevance
“…We also showed that BMI was lower in patients with IOH, and duration of surgery does not affect the occurrence of IOH, in contrast to other studies [7,11,13]. Thyroid surgery is considered to be low or moderate risk surgery.…”
Section: Discussioncontrasting
confidence: 47%
“…We also showed that BMI was lower in patients with IOH, and duration of surgery does not affect the occurrence of IOH, in contrast to other studies [7,11,13]. Thyroid surgery is considered to be low or moderate risk surgery.…”
Section: Discussioncontrasting
confidence: 47%
“…Some factors were significantly associated with postoperative mortality, including the patients’ respiratory comorbidities, postoperative cardiovascular complication, hypnotic level, anaesthetic management, type of surgery, older age; furthermore, only two studies were included in the meta‐analysis. Some studies showed that a MAP reduction more than 30% of the preoperative MAP or SBP < 90 mm Hg was associated with a higher risk of postoperative 30‐day mortality . Intra‐operative SBP < 90 mm Hg was associated with an increased risk of postoperative 1‐year mortality, but the duration of IOH were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure targets during anesthesia and critical care have been defined empirically from population data , but there is wide disagreement between clinicians about what hypotension is significant . Although hypotension is common , the incidence of hypotension is highly dependent on the definition and reporting is related to the occurrence of complications . There is little evidence that moderate hypotension is harmful and a lower safe limit could not be determined except in the extreme .…”
Section: Limitations Of Standard Domain Measurementsmentioning
confidence: 99%